Perencanaan Lanskap Kawasan Ekosistem Esensial (KEE) Untuk Pengembangan Ekowisata Mangrove di Desa Kao, Kabupaten Halmahera Utara - Sumanto Basahona; Andy Kurniawan; Ramli Hadun; Aisjah Rahmawaty Ryadin; Buhari Umasugi; Salim Abubakar (Jurnal Pertanian Khairun, 2026)
The Essential Ecosystem Area (KEE) of mangroves in Kao Village, North Halmahera Regency, covers approximately 300.92 ha and plays a significant ecological and socio-economic role. However, its utilization has not been optimally managed based on sustainability principles. This study aimed to analyze the biophysical characteristics and vegetation structure of the mangrove ecosystem and to formulate a landscape planning strategy for conservation-based mangrove ecotourism development. The research employed vegetation analysis using transect-plot methods to calculate density, frequency, dominance, and Important Value Index (IVI), ecotourism suitability analysis, and SWOT analysis to determine development strategies. The results indicated that the area is dominated by true mangrove species with high IVI values, reflecting their major role in ecosystem structure. Vegetation density ranged from dense to very dense in several zones, indicating relatively good ecosystem conditions. Suitability analysis showed that most areas are classified as suitable to highly suitable for mangrove ecotourism development. The recommended strategies include strengthening local institutions, providing environmentally friendly infrastructure, developing interpretative pathways, and enhancing community capacity through collaborative approaches. Landscape planning based on conservation zoning and limited utilization is proposed to maintain ecological and economic balance within the area.